Evaluation of micronuclei, cytomorphometric and cytologic changes of the oral mucosa in hookah and cigarette smokers - Sepulveda Inostroza, Elvira Antonieta; Bressane, Adriano [UNESP]; Schwarzmeier, Lígia Ângelo Tavares; Lacerda, Ester Borges; Anjos, Karine Rodrigues dos; Santos, Thamires Soares Procópio dos; Cavalcanti, Desiree Rosa; Nascimento, Fábio Dupart; Almeida, Janete Dias [UNESP]; Oliveira Alves, Mônica Ghislaine [UNESP] (Elsevier, 2024)
Objective: To analyze the effect of hookah and cigarettes on the oral mucosa of smokers through the use of exfoliative cytology. Study Design: Smear samples were collected by exfoliative cytology from the tongue of 33 hookah smokers, 22 cigarette smokers, and 30 non-smokers. The selected analyses include micronuclei (MN), metanuclear anomalies, epithelial maturation, and cytomorphology (nuclear area [NA], cytoplasmic area [CA], and NA/CA ratio). Results: The largest differences observed for MN and metanuclear anomalies were between cigarette smokers and the control group (notably 1 MN P = .04; total cells with MN P = .039; total MN P = .042; karyorrhexis and binucleation, P = .0001). The hookah group, compared with the control group, showed the greatest differences for karyolysis (P = .0023), binucleation (P = .0003), and broken egg (P = .008). Significant differences were found between the smokers and the control groups regarding changes in the superficial cell without nucleus, perinuclear halo, vacuolization, color change, mucus, and keratohyalin granules. There was a significant increase in the NA and NA/CA ratio in the smoker groups. Conclusion: This study showed that a combined analysis of exfoliative cytology associated with other diagnostic methods is a useful tool for studying oral carcinogenesis. Hookah and cigarettes showed similar effects in terms of displaying substantial cytogenetic and cytotoxic damage.